Efektivitas Game Epic Skater 2 Sebagai Media Simulasi Bermain Skateboard Menggunakan Konsep Fisika Kinematika 2 Dimensi - Nurul Fatihah; Nikma Nurul Khomsati; Bayu Setiaji (JFT: Jurnal Fisika dan Terapannya, 2023)
Epic Skater 2 is a 3D skating game simulating skateboarding on various tracks by sliding and spinning to get maximum points. This study aims to analyze the concept of physics in kinematics material especially parabolic motion by analyzing the trajectory objects in the y direction in the Epic Skater game is it in accordance with the concept physics then concluded its effectiveness to be applied in skateboarding. The method used is an analysis using the tracker application. By using this software tracking data is represented in the graphical form y to t. Based on the research, the maximum height obtained in the epic skater game sequentially is 0,809 m ; 0,812 m ; 0,562 m ; 0,563 m, then averange height of 0,6865 m is obtained. The maximum height obtained on the skateboard game sequentially is 0,669 m ; 0,629 m ; 0,600 m ; 0,577 m, than an averange height of 0,61875 m is obtained.